PENGARUH KOMBINASI ACUPRESSURE dan BRISK WALKING TERHADAP KADAR GULA DARAH PUASA PASIEN DIABETES MELLITUS TIPE II - Mahendra Wekoadi, Galih; Arwani, Arwani; Ari Murti Widigdo, Dwi (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Diabetes mellitus is a disease that has a characteristic sign in the form of an increase in glucose levels exceeding the normal range. The prevalence of diabetes mellitus is increasing significantly. Currently, the management of diet, exercise, and the use of pharmacological therapy are options in the management of diabetes mellitus. In addition to these therapies, there are complementary therapies such as acupressure combined with brisk walking. The purpose of this study was to prove the combination of acupressure and brisk walking intervention in influencing fasting blood glucose levels. This research was a quasi-experimental study with a non-equivalent control group design with pre-test and post-test. This study had 76 respondents with type II diabetes mellitus who were divided into 4 groups and were taken using a consecutive sampling technique. This research was conducted in Bulu Health Center Work Area, Temanggung Regency on April, 7th 2021 – May 9th 2021. The pre-test and post-test difference test used the paired t-test and the Wilcoxon test. The difference test between groups used the Kruskal – Wallis test and continued with the Post Hoc Mann – Whitney test. This study showed that there were significant differences before and after treatment in all groups (p = 0.001). The results of statistical tests also showed that the combination of acupressure and brisk walking was the best treatment for reducing blood glucose levels (p < 0.05) compared to other treatments. Complementary therapy in the form of a acupressure and brisk walking combination is the most effective treatment in reducing blood glucose levels.